Tarantula Toxin ProTx-I Differentiates Between Human T-type Voltage-Gated Ca2+ Channels Cav3.1 and Cav3.2 - Tsuyako Ohkubo; Jun Yamazaki; Kenji Kitamura (Elsevier, 2010)
ProTx-I peptide, a venom toxin of the tarantula Thrixopelma pruriens, has been reported to interact with voltage-gated ion channels. ProTx-I reduced Ba2+ currents through recombinant human T-type voltage-gated Ca2+ channels, Cav3.1 (hCav3.1), with roughly 160-fold more potency than through hCav3.2 channels. Chimeric channel proteins (hCav3.1/S3S4 and hCav3.2/ S3S4) were produced by exchanging fourteen amino acids in the hCav3.1 domain IV S3-S4 linker region and the corresponding region of hCav3.2 between each other. The ProTx-I sensitivity was markedly reduced in the hCav3.1/S3S4 chimera as compared to the original hCav3.1 channel, while the hCav3.2/S3S4 chimera exhibited greater ProTx-I sensitivity than the original hCav3.2 channel. These results suggest that the domain IV S3-S4 linker in the hCav3.1 channel may contain residues involved in the interaction of ProTx-I with T-type Ca2+ channels. Keywords:: ProTx-I, voltage-gated Ca2+ channel, hCav3.1, hCav3.2